Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s40494-019-0325-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solar radiation and environmental temperature on Art Nouveau glass windows

Abstract: This work presents the results of the evaluation of two Art Nouveau glass windows from the Casa-Museu Dr. Anastácio Gonçalves (Lisbon, Portugal) with IR-thermography during the summer solstice. According to the measurements, the surface temperature of glass depended on the outdoor environmental temperature and, mainly, on the direct solar radiation. Colored glasses presented a higher surface temperature due to the absorption of their chromophores at near-IR wavelengths. Enamels and grisailles showed higher sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…This enhanced absorbance will produce an increase in the overall temperature of the enamel and also a thermal mismatch between particles, enamel glass and base glass. The differences in the thermal expansion coefficients between particles/enamel glass and between the enamel and the base glass are expected to give rise to the formation of cracks Finally, supporting our data, recent studies using Infrared Thermography have shown that dark enamels and grisailles show an increase of the temperature 40% higher than those of the transparent glass [38,39] and about 20% higher than other colour enamels.…”
Section: Fig 5bsupporting
confidence: 90%
“…This enhanced absorbance will produce an increase in the overall temperature of the enamel and also a thermal mismatch between particles, enamel glass and base glass. The differences in the thermal expansion coefficients between particles/enamel glass and between the enamel and the base glass are expected to give rise to the formation of cracks Finally, supporting our data, recent studies using Infrared Thermography have shown that dark enamels and grisailles show an increase of the temperature 40% higher than those of the transparent glass [38,39] and about 20% higher than other colour enamels.…”
Section: Fig 5bsupporting
confidence: 90%
“…Infrared thermography has been used for a variety of art inspection and conservation cases, [ 24,25 ] including a few applications on glass materials, mostly stained‐glass windows. [ 26–30 ] The technique has proven effective in mapping the surface alteration features of archaeological glass, [ 26 ] and in distinguishing for example, soda‐lime base glass and applied lead‐glass paint in stained glass windows due to differences in heat accumulation. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 26–30 ] The technique has proven effective in mapping the surface alteration features of archaeological glass, [ 26 ] and in distinguishing for example, soda‐lime base glass and applied lead‐glass paint in stained glass windows due to differences in heat accumulation. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Until now, relatively few studies reported the use of IRT for inspecting stained glass windows. Existing publications focus on the adhesion of glass paints [4,17], manufacturing defects [18] or discuss the comparative thermal behavior of the various materials present, such as enamels, grisailles, lead cames, and welds [18][19][20]. The reported methods for data analysis are visual inspections of the thermograms [4,[17][18][19][20], temperature plots [17,19,20] and principal component analysis (PCA ) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Existing publications focus on the adhesion of glass paints [4,17], manufacturing defects [18] or discuss the comparative thermal behavior of the various materials present, such as enamels, grisailles, lead cames, and welds [18][19][20]. The reported methods for data analysis are visual inspections of the thermograms [4,[17][18][19][20], temperature plots [17,19,20] and principal component analysis (PCA ) [18]. Higher order statistical analysis of the thermograms has also been used successfully on other historical glasses to detect degradation due to ageing [21,22].…”
Section: Introductionmentioning
confidence: 99%